STUDY OF FIBER YIELD TRAIT FORMATION IN F1 HYBRID PROGENY OF G. HIRSUTUM L. WITH SYMPODIAL BRANCHING TYPE (British Journal of Global Ecology and Sustainable Development, 2026)
This article presents data obtained in 2025 on the formation of the fiber yield trait in F1 hybrid progeny resulting from crosses between introgressive forms and a number of collection varieties belonging to foreign breeding programs.